Automation in IBS: the readiness of Malaysians towards the new concept of volumetric IBS housing - Mohd Noor, Mohd Zairul; Mohamad Jamil, Mohd Azli; Azlan, Aznida; Ismail, Ida Suriana (University of Malaya, 2019)
Industrialized Building System or widely called as IBS is a new alternative in the modern construction that perceived as a ‘lean construction’. Nevertheless, a volumetric type of IBS is still unknown in the Malaysian construction industry. This paper reports the potential of future housing typology in Malaysia through the introduction of volumetric IBS called ‘flexZhouse’ in the Malaysia housing market. Surveys were conducted towards M40 and U10 respondents throughout main cities in Malaysia that involved Penang, Johor Bahru, Selangor and Kuala Lumpur respectively. The objective of the survey is to gauge the acceptance of the volumetric IBS called ‘flexZhouse’. Every questionnaire item are said to be valid because of the Cronbach’s alpha greater than 0.6. Hence, the data in this study can be classified as good and adequate for this research means. The findings could lead to a new direction of housing design for Architects and the potential market for new type of IBS in Malaysia.